Karuppunel: A promising donor for high zinc content in rice (Oryza sativa) grain - BOLLINEDI, HARITHA; NEERAJA, C N; CHATTOPADHYAY, KRISHNENDU; CHANDEL, GIRISH; SHASHIDHAR, H E; PRAKASH, JEYA; SINGH, ASHOK KUMAR; VOLETI, S R; SUNDARAM, R M (The Indian Journal of Agricultural Sciences, 2022)
Complex inheritance of high iron (Fe) and zinc (Zn) traits in polished grains, coupled with large genotype (G) × environment (E) interaction components are major challenges for rice biofortification programmes. Understanding such G × E interactions through multi-location trials and quantifying their magnitude using appropriate statistical models is the major pre-requisite in identification of stable donors for micronutrient traits for development of nutrient rich varieties. In the present study, we evaluated a set of 28 rice genotypes for Fe, Zn and key agronomical traits during wet season 2017 in 5 diverse environments in India. Combined analysis of variance revealed significant main effects due to genotypic, environmental and G × E interaction effects. Grain Fe showed maximum contribution from the effect of the genotype while in case of Zn, it was influenced significantly by environmental effect. Mega-environments were identified for stable evaluation of genotypes for Zn and Fe content, based on GGE biplot analysis. Yield stability index identified the genotype, G14 (Karuppunel) to be superior for grain Zn content (41.1 ppm) with high mean performance and high stability across the environments followed by the genotypes G4 (Taraori Basmati), G18, G25 (Tilakasturi and IC36704) and G2 (Edavankudipokkali). The findings from the study have significant implications for the development of high grain Zn containing rice varieties, so that the hidden hunger can be addressed in the right perspective.